An empirical study of physical activity and sports affecting mental health of university students - Congsheng, Lu; Kayani, Sumaira; Khalid, Amna (Frontiers in Psychology, 2022)
University students in Malaysia have poor mental health where the youth are shown to have a negative attitude due to their mental health. In the current conditions, 30% of the people in Malaysian that are aged 16 years or older are having a mental health issue. To overcome the mental health issues, physical activity and sports activity have been termed prominent; thus following study intended to test this hypothesis empirically. For this purpose, the university students from Malaysia were surveyed through social media and a 512-sample size, and around 74% response rate was recorded. For the empirical analysis, confirmatory factor analysis (CFA) was used in which structural equation model partial least square (SEM-PLS) was used. The study’s empirical findings suggest that physical activity and sports activity need to be promoted within the university students of Malaysia to control prevailing mental health issues within the youth and secure a better future for the generations to come.